APLIKASI METODE PYTHAGORAS DALAM PENYELESAIAN SOAL-SOAL RELATIVITAS KHUSUS EINSTEIN TERHADAP HASIL BELAJAR SISWA KELAS XII SMA NEGERI AMBULU - Riska Uswatun Khasanah; Bambang Supriadi; Sri Handono Budi Prastowo (JURNAL PEMBELAJARAN FISIKA, 2019)
Using the fast method is one of the categories of fast counting ability (Hardiono, 2016). One fast method is the Pythagoras method which can be used to solve special relativity questions (Korkmaz, 2016). This research an experimental research to study the student cognitive learning outcomes in solving Einstein's special relativity problems using the Pythagoras method. This research was conducted in Ambulu State High School with a population of students in class XII MIPA in semester II of the 2018/2019 academic year with samples of class XII MIPA 3 as the experimental class and class XII MIPA 1 as the control class. Each class consists of 36 students. Data obtained from documentation and learning outcomes tests in the form of written tests with 20 questions taken from national exam questions and college entrance exams. The results of the study using the Mann-Whitney test showed that the average value of the experimental class learning outcomes was higher than the control class. So this result reveals that the application of the Pythagoras method in solving Einstein special relativity questions has a significant effect on the student cognitive learning outcomes of class XII students of Ambulu High School.Key word: Einstein's special relativity, Pythagoras method, the student cognitive learning outcomes